An improved hyperplane projection method for generalized Nash equilibrium problems with extrapolation technique. (3rd October 2022) - Jia, Xiaoxi; Sun, Zhiren; Xu, Lingling
Abstract : The generalized Nash equilibrium problem is a kind of noncooperative game, whose strategy set of each player depends on the other rivals' decisions. Projection-type methods can be used to solve the corresponding quasi-variational inequalities problem. In this paper, we propose an accelerated method based on the half-space projection algorithm. At each iteration, we get a prediction point firstly by the half-space projection method. Then we use the extrapolation technique to obtain the next iterate. Numerical results show that our algorithm is effective.